2020
DOI: 10.3390/polym12122942
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Composite Dust Suppressant for Coal Mines

Abstract: In an effort to effectively control coal dust pollution and thereby reduce the harm of coal dust to human health, we prepared a highly efficient composite dust suppressant. First, dynamic contact angle and zeta potential measurements were used to select sodium dodecyl sulfonate (SDS) over sodium carboxymethyl cellulose and trisodium methyl silicon as the complementary additive to soy protein isolate for the dust suppressant. We employed viscosity and wind erosion resistance tests to compare the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…After comparing the effects of road surface cleaning, water flushing, and chemical dust suppressants upon reducing the dust in the surrounding environment, Anderson [19] found that chemical dust suppressants demonstrate the most obvious effect on fugitive road dust suppression. Jin [20][21][22] developed a new type of biodegradable environmentally friendly dust suppressant and a highly efficient composite dust suppressant which can effectively inhibit the re-entrainment of coal dust and reduce environmental pollution. Gang [23] developed a chemical dust suppressant for tarmac roads.…”
Section: Introductionmentioning
confidence: 99%
“…After comparing the effects of road surface cleaning, water flushing, and chemical dust suppressants upon reducing the dust in the surrounding environment, Anderson [19] found that chemical dust suppressants demonstrate the most obvious effect on fugitive road dust suppression. Jin [20][21][22] developed a new type of biodegradable environmentally friendly dust suppressant and a highly efficient composite dust suppressant which can effectively inhibit the re-entrainment of coal dust and reduce environmental pollution. Gang [23] developed a chemical dust suppressant for tarmac roads.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment on physical and chemical properties allows for the observation of the structural characteristics of the main components of the dust suppressant. Scanning electron microscopy (SEM) was utilized to observe the microstructure of the dust suppressant and the morphology of the curing layer after combination with dust particles [49]. The functional group changes and internal structure mechanism of dust suppressors were observed by Fourier infrared spectroscopy (FTIR) and X-RD.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…According to data from the United States Environmental Protection Agency for 2014 [ 8 ], the main sources of dust included wildfires, non-road and on-road dust, industrial processes, and fuel combustion, where industrial processes contributed the most to pollution, at 63% and 87% for PM2.5 and PM10, respectively. Coal mining contributes highly to pollution; therefore, much of the recent work has been devoted to creating effective dust suppressors for coal particles [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. If we consider dust sources in cities far from industrial centers and do not consider wildfires, then the main source of dust is road dust, at 48% and 62% for PM2.5 and PM10, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%